Relationships of experiential marketing and experiential value in predicting tourists’ satisfaction on Kelantan food / Nurul Syahida Hawalis - Hawalis, Nurul Syahida (2013)
Known as a Cradle of Malay Culture, Kelantan is famous for its distinctive cultural heritage, natural environments, and unparalleled hospitality of the locals including their unique foods which have influenced the development of the tourism industry. In relation to that, Kelantan Tourism Malaysia together with the help of corporate organizations aggressively promotes Kelantan food products locally and internationally. However, it raises critical questions of how tourists perceived Kelantan food during their visits. Thus, this study was to offer an approach to understand the relationships between experiential marketing, experiential value and tourists’ satisfaction on Kelantan food. A total of two hundred and eight (208) international tourists’ visited Kota Bharu, PengkalanChepa and KubangKerian area had participated in this study. Data were gathered through self-administered survey questionnaires and the results revealed that experiential marketing (β=.872, p<0.001) and experiential value (β=.853, p<0.001) have positive relationships with tourists’ satisfaction. In addition, this study also found that experiential value partially mediated the relationship between experiential marketing and tourists’ satisfaction. Implication and recommendations for future research are also provided in this study.